2015
DOI: 10.1097/ede.0000000000000171
|View full text |Cite
|
Sign up to set email alerts
|

School Performance After Preterm Birth

Abstract: Our study suggests that the association between school performance and preterm birth after 30 gestational weeks is attributable to factors other than preterm birth per se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 22 publications
2
47
1
Order By: Relevance
“…Large Scandinavian register-based data analyses have found associations between preterm birth and a wide range of educational, social, cognitive and mental health outcomes in adolescence and young adulthood [24, 18, 2327]. However, a causal relationship between preterm birth and cognition was recently questioned in a Swedish analysis which showed that the effect of preterm birth (<30 weeks) on low school grades attenuated in sibling analyses[28]. …”
Section: Discussionmentioning
confidence: 99%
“…Large Scandinavian register-based data analyses have found associations between preterm birth and a wide range of educational, social, cognitive and mental health outcomes in adolescence and young adulthood [24, 18, 2327]. However, a causal relationship between preterm birth and cognition was recently questioned in a Swedish analysis which showed that the effect of preterm birth (<30 weeks) on low school grades attenuated in sibling analyses[28]. …”
Section: Discussionmentioning
confidence: 99%
“…3 Increased utilization of resources in early life, increased need for early intervention services, and reduced school performance are more common among survivors of preterm birth, resulting in significant societal costs. 46 …”
Section: Introductionmentioning
confidence: 99%
“…Following the advances in perinatal care, an increasing number of preterm infants reach childhood (2). Negative effects of preterm birth on neurodevelopmental and psychiatric development of children and adolescents have been well documented (3)(4)(5)(6)(7)(8). Severe neurological impairment has been reported in 10 to 12% of school-aged children, who were born very preterm (less than 32 weeks of gestation) (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%